(untitled) (Applied Biological Research, 2012)
Hydatidosis is one of the important zoonotic diseases caused by larval stages of Echinococcus granulosus with economic implications in terms of reduction in livestock production due to condemnation of infected organs of slaughtered animals (Umur and Kaaden, 2003). Buffaloes act as one of the intermediate hosts of parasite harbouring hydatid cyst mainly in organs like liver and lungs and has also been reported from several parts of India (Dhote et al., 1992; Sharma et al., 2000). The present communication reports hydatid cysts in Murrah buffaloes from Punjab (India).